Exploring Past Myths through Giambattista Vico and Jyotiba Phule - Aparna Devare (Contexto Internacional)
Abstract In this article, I examine the writings of the 18th-century Italian thinker Giambattista Vico and the 19th-century Indian thinker/social reformer Jyotiba Phule about myths, temporality, and the past. Both these thinkers turned to historicising myths in order to engage with debates in the present. Both viewed myths as reflecting social relations of power and domination, and sought to understand their material realities, emphasising human agency, collective change, and the social construction of language and practices. Both pointed to the limits of history, albeit in different ways: Vico by introducing the notion of providence, and Phule by rewriting the myths he had rationalised, using the same mythological figures, in order to intervene in the politics of the present from a marginal perspective (that of being low-caste). I juxtapose these two disparate thinkers in terms of their similarities in historicising myths, and analyse why Phule goes further than Vico in exceeding the boundaries of history. I argue that Phule’s cultural context allowed him to return to myths more easily than Vico, although the latter revered them as well.